Caracterização farmacognóstica, química, físico-química e estudos preliminares de pré-formulação da Arrabidaea chica (Humb. & Bonpl.) B. Verlt. - ALVES, Mauro Sérgio Marques (Universidade Federal do Pará, 2011)
This work aimed the physical, chemical, physico-chemical and preformulations characterizing of Arrabidaea chica (Humb. & Bonpl.) B. Verlt., belonging to the family of Bignoniacae, which receives several denominations, and in the Amazon region is known popularly as pariri, that is widely used in popular medicine for the treatment of many diseases, such as skin infirmities caused by dermatitis and eczema. The use of natural products from vegetal origin requires the pharmaco-botanical quality control and pureness analysis which sets the species technical specifications. Therefore, it was made an anatomical description of the young and mature leaves of the plant from observations made at the optic microscope in histological cuts. The pharmacological tests included the determination of the granulometrical distribution of the plants powder, determination of the humidity purport and of total ashes and, about the dyeing, it was made pH, relative density and solids purport determinations, and also it was made the chemical prospection, the chromatographic profile by thin-layer chromatography (TLC) and the highperformance liquid chromatography (HPLC), besides the valuation of its microbial activity. To the powder as well as the dyeing of the A. chica observed the profiles by spectroscopy in the infrared region and thermal profiles by TGA and DTA. Some studies of preformulation were made by spectroscopy in the infrared region and thermal analysis (TGA and DTA) of the binary mixtures of the formula adjuvants suggested to spread the dye, with the purpose to evaluate possible incompatibilities between the dye and these elements. The results obtained evidenced that the A. chica dye demonstrated to adjust to the aim demanded, moreover it assured the compatibility to the tested adjuvants to constitute the proposed formula, once none clue of physical or chemical incompatibilities were observed among them. The studies provided relevant basis to the development of the proposed formula, seeking to obtain quick results with the wished accuracy.